2015
DOI: 10.1152/ajpregu.00191.2015
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor activation is involved in the control of daily torpor in a seasonal mammal

Abstract: Scherbarth F, Diedrich V, Dumbell RA, Schmid HA, Steinlechner S, Barrett P. Somatostatin receptor activation is involved in the control of daily torpor in a seasonal mammal. Am J Physiol Regul Integr Comp Physiol 309: R668 -R674, 2015. First published July 8, 2015 doi:10.1152/ajpregu.00191.2015 show spontaneous daily torpor only after ϳ2 mo in winter-like short photoperiods (SP). Although some SP-induced hormonal changes have been demonstrated to be necessary for the occurrence of seasonal torpor, the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
(33 reference statements)
2
17
0
Order By: Relevance
“…SDT is a period of hypometabolism and hypothermia (Tb< 32°C) that occurs unpredictably during the light phase for 0.5-11 hours, even without obvious challenges like low Ta or food restriction (Heldmaier and Ruf, 1992;Ruf et al, 1993). Although different hormonal systems (testosterone, leptin, somatostatin) have been shown to be involved in the expression of spontaneous torpor, the exact driving mechanisms for torpor are still unclear (Freeman et al, 2004;Scherbarth et al, 2015;Vitale et al, 1985).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…SDT is a period of hypometabolism and hypothermia (Tb< 32°C) that occurs unpredictably during the light phase for 0.5-11 hours, even without obvious challenges like low Ta or food restriction (Heldmaier and Ruf, 1992;Ruf et al, 1993). Although different hormonal systems (testosterone, leptin, somatostatin) have been shown to be involved in the expression of spontaneous torpor, the exact driving mechanisms for torpor are still unclear (Freeman et al, 2004;Scherbarth et al, 2015;Vitale et al, 1985).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Our results suggest that an increased use of torpor seems to conflict with the energy-demanding processes of structural growth. Supporting evidence for this hypothesis is provided by a recent study of Scherbarth et al (2015) showing that a suppression of growth hormone secretion via pasireotide, an analog of the growth hormone release inhibiting hormone somatostatin, increased the incidence of daily torpor in Siberian hamsters ( Phodopus sungorus ) exposed to a (winter-like) short photoperiod. Hence, high levels of growth hormone required for the activation of the growth axis may prevent individuals from entering a torpid state.…”
Section: Discussionmentioning
confidence: 94%
“…Spontaneous daily torpor only occurs when adaptations of fur, body weight and gonads are completed and it has been shown that the accompanying reductions in prolactin, leptin, growth hormone and testosterone are permissive for torpor behavior (Ruby et al 1993, Freeman et al 2004, Scherbarth et al 2015. When these hormones are supplied, they are able to reduce torpor incidence or entirely block torpor.…”
Section: Endocrine and Energetic Control Of Daily Torpormentioning
confidence: 99%